Pengaruh Laba Bersih, Arus Kas Dan Dividen Tunai Terhadap Volume Perdagangan Saham Pada Perusahaan Publik Sektor Barang Dan Konsumsi Di BEI - Etty Susilowati; Hernawati Sinaga (Universitas Islam Kadiri, 2019)
The stock trading volume is the number of shares that are traded on the capital market every trading day with a price level agreed upon by the seller and buyer through an intermediary in the capital market. Stocks will be more liquid with the amount of investment in shares. To assess the volume of stock trading, investors can evaluate net income, cash flow and cash dividends. The purpose of this study was to analyze the effect of net income, cash flow and cash dividends on the volume of stock trading in 10 public goods and consumption sectors listed on the Indonesia Stock Exchange (IDX) through a purposive sampling technique both simultaneously and partially. The research data were analyzed using multiple linear regression methods. The results of this study indicate that simultaneously net income, cash flow and cash dividends have significant effects on the volume of stock trading of public companies in the goods and consumption sector, while partially, only net income (β = 0.485) and cash flow (β= 1.587) have significant positive effects against the volume of stock trading.